Influence of pH and calcium nutrition on the coffee wilt caused by fusarium oxysporum - Cardoso, Rogério M.L.; Ota, Hatsuyo; Pavan, Marcos A. (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse solution experiment was conducted with coffee seedlings to investigate the effects of Ca nutrition and pH on growth, plant nutrient content, and the incidence of Fusarium oxysporum f. sp. coffeae. Five concentrations of Ca (0, 10, 100, 200 and 400 µg ml-1) were maintained in combination with two pH levels (4.5 and 6.5). Suspensions of the fungus were inoculated at the colon region of seedlings after 105 days of cotyledon emergency. Dry weight yields increased with increasing Ca levels up to 100 µg ml-1 followed by a marked decrease when Ca concentration was raised to 200 - 400 µg ml-1' of Ca. Plant tissue analysis showed that increasing Ca levels in solution increased the uptake of Ca and N, decreased P, K, Mg, Mn and Fe, and had no effect on Cu and Zn. The extent of colonization of the vascular tissues by the fungus was greater at pH 6.5 than 4.5. The percentage of root and stem tissues incited by the fungus mycelium was increased at low Ca treatments (0 and 10µg of Ca ml-1). The severity of disease generally decreased with increasing Ca in solution up to 200 and 400µg ml-1.